Shakespeare's late work - Lyne, Raphael (Oxford Shakespeare topics., 2007)
This introduction to Shakespeare's work offers clear but ambitious readings of the late plays. It incorporates collaborative works, revised works, and textual analyses in its discussion of the characteristics of this phase in Shakespeare's career. It also considers its relationships with the work of Fletcher, Middleton, and with Shakespeare's earlier work. - ;Shakespeare's Late Work is a detailed reading of the plays written at the end of Shakespeare's career, centring on Pericles, Cymbeline, The Winter's Tale, and The Tempest. Unlike many previous studies it considers all the late work, inclu.